2004
DOI: 10.1111/j.0022-202x.2004.22504.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate of Bullous Pemphigoid in a US Medical Center

Abstract: All patients at the Medical College of Wisconsin Affiliated Hospitals with a new diagnosis of bullous pemphigoid (BP) between May 1, 1997 and September 1, 2002 were included in this study. The age at onset, date of death or date of last follow-up visit, mode of treatment, co-morbidities, and initial and follow-up hospitalizations were noted. Thirty-eight new patients were identified and complete follow-up data were obtained on 37 of the patients. Patients were followed a minimum of 1 y or until the time of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 20 publications
6
79
3
5
Order By: Relevance
“…Interestingly, although a recent study including 223 patients found a 1-year mortality rate of 23% [17], two reports from the USA demonstrated a 1-year mortality rate of 10.8 and 15%, respectively, whereas another study found a 2-year mortality rate of 6% [28,29,30]. The latter figures probably reflect differences in patients' recruitment between European and USA centers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although a recent study including 223 patients found a 1-year mortality rate of 23% [17], two reports from the USA demonstrated a 1-year mortality rate of 10.8 and 15%, respectively, whereas another study found a 2-year mortality rate of 6% [28,29,30]. The latter figures probably reflect differences in patients' recruitment between European and USA centers.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the poor prognosis of these patients may be responsible for the observed difference of BP patients’ survival rate between Europe and the United States [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda ise kadın erkek oranı yaklaşık olarak birbirine eşit bulunmuştur. Tanı anındaki ortalama yaş değerlendirildiğinde 70,17±16,98 yıl olarak saptadı, bu değer literatürle uyumlu bulundu (73,7-82,4±7,4 yıl) 6,8,9,19,20 . Literatürlerde yaşlı popülasyonda erkek cinsiyet hakimiyeti bulunmuştur 2,11,12 .…”
Section: Introductionunclassified
“…Avrupadan, BP'nin bir yıllık mortalite oranlarına yönelik çok çeşitli yayınlar mevcuttur. Bu çalışmalarda mortalite oranı %10,8-41 olarak belirlenmiştir 20,21,24,25 . Ülkemizden Akay ve arkadaşlarının yaptıkları çalışmada ise mortalite oranı %19,3 olarak hesaplanmıştır 16 .…”
Section: Introductionunclassified